2011
DOI: 10.1111/j.1472-4642.2011.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of long‐distance seed dispersal in the local population dynamics of an invasive plant species

Abstract: Aim  Long‐distance dispersal is important for plant population dynamics at larger spatial scales, but our understanding of this phenomenon is mostly based on computer modelling rather than field data. This paper, by combining field data and a simulation model, quantifies the fraction of the seed of the alien species Heracleum mantegazzianum that needs to disperse over a long distance for successful invasion.Location  Central Europe, Czech Republic.Methods  To assess the role of random dispersal in long‐term po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 71 publications
0
50
0
1
Order By: Relevance
“…Natal grass seeds are light; a gram contains from 1,311 to 1,417 (21) . The small weight of the seed and its plumose characteristics are attributes for an efficient and fast dispersion (39,40,41) .…”
Section: Seed Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natal grass seeds are light; a gram contains from 1,311 to 1,417 (21) . The small weight of the seed and its plumose characteristics are attributes for an efficient and fast dispersion (39,40,41) .…”
Section: Seed Productionmentioning
confidence: 99%
“…Las semillas de rosado son livianas; un gramo contiene de 1,311 a 1,417 (21) . El peso de la semilla y su característica plumosa le confieren atributos para una eficiente y rápida dispersión (39,40,41) .…”
Section: Producción De Semillaunclassified
“…In its native range, P. mahaleb was shown to disperse seeds at considerable distances, reaching over 900 m, but local seed movements dominate, similarly to P. serotina (García et al 2007). The role of long distance dispersal is one of the focal points in studies on biological invasions, emphasizing the great invasive potential of frugivorous species (Von Der Lippe and Kowarik 2007; Vanhellemont et al 2010;Pergl et al 2011;Amodeo and Zalba 2013). Gosper et al (2005) showed that the structure of the landscape, i.e.…”
Section: Colonization In Agricultural Landscape Vs Forest Complexmentioning
confidence: 99%
“…The long-distance component can be as simple as global dispersal that is independent of distance (Pergl et al, 2011;Hester and Cacho, 2012). More advanced approaches use mechanistic simulation algorithms for the long-distance dispersal.…”
mentioning
confidence: 99%
“…However, we still scored Cluster F as being of medium suitability for investigating the effectiveness of phytosanitary measures because the flexibility to include multiple dispersal mechanisms means there should be potential to model dispersal through trade. For example, Epanchin-Niell et al (2012) present a model in which new populations enter from outside the modelled domain randomly in both space and time, which bears strong similarity to the models using global dispersal for long-distance spread (Pergl et al, 2011;Hester and Cacho, 2012).…”
mentioning
confidence: 99%